Landmark ctDNA Molecular Response Represents an Early Predictor of Immunotherapy Outcomes in Lung Cancer: A Clinical Validity Study - Noushin Niknafs; Lavanya Sivapalan; Archana Balan; Jaime Wehr; Gavin Pereira; Samira Hosseini-Nami; Nisha Rao; Shreshtha Jolly; Kavya Velliangiri; Iiasha Beadles; Tiffany Loftus; Bryan Chesnick; et al. (Clinical Cancer Research, 2026)
Abstract Purpose: Circulating tumor DNA (ctDNA) analyses are informative as an early indicator of immunotherapy response in advanced non–small cell lung cancer (NSCLC); however, the clinical value of ctDNA molecular response (mR) requires further validation. Experimental Design: As part of a prospective clinical protocol (NCT05995821), we conducted targeted error-correction sequencing of ctDNA (n = 328) and matched white blood cell (WBC) DNA (n = 109) from 109 patients with metastatic NSCLC who received anti–PD-(L)1 either as monotherapy or in combination. Following cellular origin resolution of 2,818 variants, landmark mR was defined as undetectable ctDNA within 3 to 9 weeks of treatment initiation. Results: Pre-treatment ctDNA burden, but not blood tumor mutation burden, predicted survival. Implementing a tumor-naïve WBC DNA-informed approach increased the number of evaluable cases without compromising the overall accuracy of landmark ctDNA mR. A direct comparison of single-timepoint on-therapy ctDNA assessment with ctDNA dynamics from baseline to the 3- to 9-week interval, along with an analysis of heterogeneity in mR within the 3- to 9-week window, showed that undetectable ctDNA at the landmark timepoint can effectively predict survival outcomes. A significant enrichment in landmark ctDNA mR was noted among patients with progression-free survival (PFS) ≥6 months on immunotherapy (P = 2.5e−05) or chemoimmunotherapy (P = 0.02). Patients in the landmark mR group had longer PFS (P = 1.6e−06) and overall survival (P = 2.5e−05) than those with molecular progression. Conclusions: Landmark ctDNA mR provides a real-time, accurate approach for monitoring immunotherapy clinical outcomes. Although not currently validated for regulatory use, these findings demonstrate the potential validity of ctDNA as an early endpoint of immunotherapy response.